EFEKTIVITAS PROGRAM SANTUNAN INSENTIF ANAK DIDIK ( SIADIK) LAZNAS SAHABAT YATIM INDONESIA DI KOTA MEDAN DARI TAHUN 2018-2022 - Aufa Khirman Fadhillah; Andri Soemitra; Mustafa Kamal Rokan (Jurnal Akuntansi dan Pajak, 2023)
Education is a very fundamental right for children. The programs run by LAZNAS Sahabat Yatim Indonesia certainly have their own goals as well as educational programs, one of which is SIADIK which has the goal of providing a little pocket money assistance from what you set aside to help develop their smiles when they can enjoy their school snacks and can get proper and better education. Intensive student compensation (SIADIK) is a program from the Indonesian orphan friend foundation to overcome poverty in studying, and to participate in helping the government in overcoming poverty to create a quality society in various aspects of the field because new generations will emerge who have skills in building a nation. Besides that, the effectiveness of the Intensive Compensation Program for Students (Siadik) Laznas Friends of Indonesian Orphans is needed, especially in the city of Medan. This research is descriptive with a qualitative approach. Descriptive research has characteristics that can reveal or dissect various natural and social phenomena in society specifically. The research results of the Student Incentive Compensation Program (SIADIK) conducted by the National Amil Zakat Institute (LAZNAS) Sahabahat Yatim Indonesia in the city of Medan, namely by searching for children who will receive assistance to schools or to the surrounding environment, requesting data necessary, and distribute funds directly to children who will receive the compensation. The effectiveness of the assistance carried out by LAZNAS Sahabat Yatim Indonesia in the city of Medan can be seen from the satisfaction and use of the money by the children.